Perancangan Enterprise Architecture E-Procurement Framework Architecture Development Method (ADM) Pada Krakatau Steel di Cilegon - Anita Megayanti (Universitas Insan Cendekia Mandiri, 2022)
E-Procurement is a process of procuring goods or services electronically and facilitated by software or a website with an internet connection. An enterprise design model for the eprocurement application architecture aims to serve as a guide in developing eprocurement at Krakatau Steel in accordance with the needs and objectives of the logistics division of Krakatau Steel. The research method uses TOGAF ADM architectural modeling by conducting interviews and observations. And there are several stages that are implemented, namely the Preliminary Stage, Architecture Vision, Business Architecture, Information System Architecture, Technology Architecture, Opportunities and Solutions. The results found in this study are the integration of the eprocurement application with the MM module SAP application so that the goods/services procurement process activities can run as expected. In addition, it can also produce blueprints as the basis for the e-procurement process enterprise design strategy at Krakatau Steel.